Text Treasures: Nag Hammadi Codices (2020)
The Nag Hammadi Codices are a group of papyrus manuscripts discovered near the city of Nag Hammadi in southern Egypt, about 70 miles north of Luxor. The codices (i.e., bound volumes) contain writings that shed light on the diverse religious and philosophical currents of the early Christian period.
Keywords: Egypt; Egyptians; Farmers; Manuscripts; Nag Hammadi Codices